Hepatic Sirt1 deficiency in mice impairs mTorc2/Akt signaling and results in hyperglycemia, oxidative damage, and insulin resistance - Rui-Hong Wang; Hyun‐Seok Kim; Cuiying Xiao; Xiaoling Xu; Oksana Gavrilova; Chu‐Xia Deng (2011)
Insulin resistance is a major risk factor for type 2 diabetes mellitus. The protein encoded by the sirtuin 1 (Sirt1) gene, which is a mouse homolog of yeast Sir2, is implicated in the regulation of glucose metabolism and insulin sensitivity; however, the underlying mechanism remains elusive. Here, using mice with a liver-specific null mutation of Sirt1, we have identified a signaling pathway involving Sirt1, Rictor (a component of mTOR complex 2 [mTorc2]), Akt, and Foxo1 that regulates gluconeogenesis. We found that Sirt1 positively regulates transcription of the gene encoding Rictor, triggering a cascade of phosphorylation of Akt at S473 and Foxo1 at S253 and resulting in decreased transcription of the gluconeogenic genes glucose-6-phosphatase (G6pase) and phosphoenolpyruvate carboxykinase (Pepck). Liver-specific Sirt1 deficiency caused hepatic glucose overproduction, chronic hyperglycemia, and increased ROS production. This oxidative stress disrupted mTorc2 and impaired mTorc2/Akt signaling in other insulin-sensitive organs, leading to insulin resistance that could be largely reversed with antioxidant treatment. These data delineate a pathway through which Sirt1 maintains insulin sensitivity and suggest that treatment with antioxidants might provide protection against progressive insulin resistance in older human populations.